Cytosolic Invertase-Mediated Root Growth Is Feedback Regulated by a Glucose-Dependent Signaling Loop. Issue 2 (20th August 2020) - Meng, Lai-Sheng; Wei, Zhi-Qin; Cao, Xiao-Ying; Tong, Chen; Lv, Meng-Jiao; Yu, Fei; Loake, Gary J.
Abstract : An Arabidopsis cytosolic Invertase is dynamically regulated by a glucose signaling feedback loop to control root growth Abstract: The disaccharide Suc cannot be utilized directly; rather, it is irreversibly hydrolyzed by invertase to the hexoses Glc and Fru to shape plant growth. In this context, Glc controls the stability of the transcription factor Ethylene-Insensitive3 (EIN3) via the function of Hexokinase1 (HXK1), a Glc sensor. Thus, invertase, especially the major neutral cytosolic invertase (CINV), constitutes a key point of control for plant growth. However, the cognate regulatory mechanisms that modulate CINV activity remain unclear. Here, we demonstrate that in Arabidopsis ( Arabidopsis thaliana ), EIN3 binds directly to both the promoters of Production of Anthocyanin Pigment1 ( PAP1 ) and Phosphatidylinositol Monophosphate 5-Kinase 9 ( PIP5K9 ), repressing and enhancing, respectively, their expression. Subsequently, PAP1 binds directly to and promotes transcription of the Cytosolic Invertase1 ( CINV1 ) promoter, while PIP5K9 interacts with and negatively regulates CINV1. The accumulated CINV1 subsequently hydrolyzes Suc, releasing the sequestered signaling cue, Glc, which has been shown to negatively regulate the stability of EIN3 via HXK1. We conclude that a CINV1-Glc-HXK1-EIN3-PAP1/PIP5K9-CINV1 loop contributes to the modulation of CINV1 activity regulating root growth by Glc signaling.